My First Aeroplane Journey - Boli, Geyin (THE PRIMARY TEACHER, 2019)
As the title suggests, the book is about a pictorial expression, inviting the readers to share the experiences of a little girl and her first aeroplane journey. It presents the perspective of a little girl who excitedly and curiously experiences her first aeroplane journey. The detailed aeroplane journey is shared with the use of child-friendly illustrations on the whole, the book acts as a package of information almost like a virtual aeroplane travel tour from children’s point of view